2014
DOI: 10.3233/jpd-140388
|View full text |Cite
|
Sign up to set email alerts
|

In a Rush to Decide: Deep Brain Stimulation and Dopamine Agonist Therapy in Parkinson's Disease

Abstract: Background: It has been suggested that all patients with Parkinson's disease (PD) who undergo functional neurosurgery have difficulties in slowing down in high conflict tasks. However, it is unclear whether concomitant dopaminergic medication is responsible for this impairment. Objective: To assess perceptual decision making in PD patients with bilateral deep brain stimulation. Methods: We tested 27 PD patients with bilateral deep brain stimulation on a task in which participants had to filter task relevant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Compulsive behaviours in OCD may be an attempt to accumulate sufficient evidence to commit to a decision and may be influenced by the degree of uncertainty. Deep brain stimulation targeting the subthalamic nucleus has shown an influence on the RDMT in patients with Parkinson’s disease (Green et al , 2013) but not on a perceptual decision task (Djamshidian et al , 2014); further studies exploring these differences and particularly in OCD patients may be indicated. Our results highlight the differential role of implicit incentives and external feedback in decision formation in OCD.…”
Section: Resultsmentioning
confidence: 99%
“…Compulsive behaviours in OCD may be an attempt to accumulate sufficient evidence to commit to a decision and may be influenced by the degree of uncertainty. Deep brain stimulation targeting the subthalamic nucleus has shown an influence on the RDMT in patients with Parkinson’s disease (Green et al , 2013) but not on a perceptual decision task (Djamshidian et al , 2014); further studies exploring these differences and particularly in OCD patients may be indicated. Our results highlight the differential role of implicit incentives and external feedback in decision formation in OCD.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the aim of this study was to assess cognitive impulsivity, specifically reflection impulsivity and perceptual decision‐making, in drug naïve RLS patients and those treated with DT. The Pixel task (assessing perceptual decision‐making) and the Beads task (assessing reflection impulsivity) have been used in a large cohort of patients with and without behavioral addictions. In both tasks, information has to be sampled.…”
Section: Introductionmentioning
confidence: 99%
“…This could potentially be problematic and result in test-retest effects confounding the results. In addition, not all studies included HCs [33][34][35][36] and thirteen studies [23,[27][28][29]33,35,[37][38][39][40][41][42][43] did not test patients off medication, which contributes to the uncertainty about effects of medication. Thus, it remains unclear to what extent decision-making is impaired in PD and to what degree dopaminergic medication impacts decisionmaking processes.…”
Section: Methodsmentioning
confidence: 99%
“…Studies demonstrated a higher occurrence of irrational choices and a tendency to gather less information before making decisions and make faster decisions (i.e. jumping to conclusions) in patients on medication compared to patients off medication [32,52] as well as in patients receiving polytherapy (L-dopa and DA) relative to L-dopa monotherapy [37,38,43]. Seinstra et al [36] found no effects of DBS or dopaminergic medication when measuring delay-discounting behavior, used to evaluate impulsive choice.…”
Section: Uncategorized Tasksmentioning
confidence: 99%